Residual Strength Analysis of Oil and Gas Pipelines with Different Corrosion Depths - Wang, Jiajie; Fan, Yi; Hu, Tinglong; Li, Yesai (International Journal of Natural Resources and Environmental Studies, 2025)
In this study, a finite element model has been created to evaluate the residual strength of oil and gas pipelines under varying degrees of corrosion. In pipelines affected by corrosion, the highest stress typically concentrates in the damaged area due to the detachment of material caused by corrosion, which weakens the pipeline’s structural integrity. The maximum stress varies with different levels of defect depth; as the defect becomes more severe, the peak stress in the pipeline increases. If the defect depth remains below 6 mm, the pipeline’s strength is sufficient to meet operational requirements and prevent failure.